Observation of dipolar splittings in high-resolution atom-loss spectroscopy of 6Li p-wave Feshbach resonances - Gerken, Manuel; Tran, Binh; Weidemüller, Matthias (Physical review, 2019)
We report on the observation of dipolar splitting in 6Lip-wave Feshbach resonances by high-resolution atom-loss spectroscopy. The Feshbach resonances at 159, 185, and 215G exhibit a doublet structure of 10, 6, and 13mG, respectively, associated with different projections of the orbital angular momentum. The observed splittings agree well with coupled-channel calculations. We map out the temperature dependence of the atom-loss spectrum and extrapolate resonance positions as well as the corresponding widths to zero temperature. The observed dipolar splitting in fermionic lithium might be useful for the realization of the quantum phase transition between the polar and axial p-wave superfluid phases.
Gesehen am 30.03.2020
Im Haupttitel ist die "6" hochgestellt